Democratization in Africa: Double Standards in Benin and Togo - Houngnikpo, Mathurin (Tufts Archival Research Center, 2005)
Volume 25, Issue 2. Summer The author takes a critical look at France's differing approach to the promotion of democracy in two of its former African colomes, Togo and Benin.